Study of knowledge and practices related to handwashing in school going children of a rural community - Pratinidhi, S. A.; Haribhakta, S. V.; Ambike, D. A.; Bhole, Om; Kankariya, Bhavesh (International Journal of Contemporary Pediatrics, 2019)
Background: A questionnaire-based study was conducted in rural schools of Maval taluka of Pune district to assess the knowledge about hand washing practices and behavior in school going children. It is well known that hand contamination plays a major role in faeco-oral transmission of diseases. Hand washing is well recognized preventable tool in disease prevention. Methods: A questionnaire-based study on hand washing practices and behavior in school going children in Maval taluka was carried out on 340 volunteers (students) from grade 6 to 8 of rural area of Maval taluka, Pune District. Maharashtra. Statistical analysis was done by using percentages and proportions. Results: A total of 340 students from grade 6 to 8 participated in the study. Majority were from age 11-13 years (n= 147). Almost all (n=320, 93%) were knowing the practice of handwashing. Majority (n=209,61%) were using soap in some form for cleaning of hands. Many (n=250,73%) were having practice of washing hands before meals. Almost all (n=309, 91%) were knowing the reason for washing of hands. The benefits and prevention of diseases were known to majority of students (n= 295,87%) Nail trimming was done once a week in almost all students.(n=250,73%) Reason for trimming of nails was known to many (n=326, 96% ) as it prevents the spread of the disease, only (n=14,4% ) were not aware of the reason for trimming of the nails. About (n=201, 59 %) of mothers had formal education upto tenth std. Conclusions: Majority of the students used water and soap for hand washing and knew the importance of hand cleaning to prevent many diseases.